Plurima mortis imagoPodoba mnohotvárnej smrti - Profantová, Zuzana (Studia mythologica Slavica, 2006)
/The image of multiple death/ The author of this contribution presents the image of death in genres of the Slovak folklore. She focuses her attention on the signs of death in a traditional environment with special attention paid to the omens and signs of death in dreams. She is looking for analogies in folkloristic materials with C. Jung’s hypotheses about dreams and with M. Eliade`s theory of rituals. The image of death as a bride, which on a symbolic level means an initiation, is the dominant feature for the entire body of the material. The image of the white bride- death has an archetypal character.